Fluid Brilliance: Expanding the Horizons in MIMO Diversity Using Liquid Antenna - Viswanadh Raviteja Gudivada; Yi Huang (IEEE Open Journal of Antennas and Propagation)
A six-port liquid dielectric resonator antenna designed to enhance diversity for Wi-Fi applications operating at 2.45 GHz, leveraging the fluidic properties of liquids is presented. The proposed design incorporates both conventional and modified intrusive feeding mechanisms, specifically utilizing extended copper lines with vertical dielectric wall support. This arrangement is aimed at realizing six pattern and polarization-independent TM $_{0}2δ {+}1 $ , HEM ${^{\text {y}}} {_{2}1δ {+}1 }$ , HEM $1{_{2}2δ }$ , HEM $2{_{2}2δ }$ , HEM ${^{\text {x}}} {_{2}1δ {+}1 }$ , and HEM ${^{\text {y}}} {_{1}2δ {+}1 }$ higher-order modes belonging to the TM and HEM mode family. The liquid antenna demonstrates favorable MIMO characteristics and satisfactory far-field behavior, all within a compact profile of less than $0.24λ $ o. A working prototype is designed and tested with good agreement between the simulated and the measured results.